PERSEPSI DIRI DALAM MEMBACA PADA PEMELAJAR BAHASA INGGRIS DI PERGURUAN TINGGI - Miftahul Furqon; Shelia Anjarani; Fatin Rohmah Nur Wahidah (Universitas Muhammadiyah Purwokerto, 2023)
Viewed from the theoretical and practical point of view, students' self-perceptions on reading comprehension aspects can be used as a reference for pedagogical practices which can overcome the problems in understanding reading English texts. Referring to the importance of knowing the aspects of English learners in reading, this study identifies and analyzes the self-perceptions of English learners in reading. As the main data, scores on the self-perception scale in reading were collected from a self-perception survey using the Reader Self-Perception Scale (RSPS) questionnaire. The main data in the form of four aspects of self-perception, namely progress (P), observational comparison (OC), social feedback (SF), and physiological state (PS) were analyzed qualitatively to determine the level of each aspect/dimension of self-perception studied. This study found that the progress aspect was in a low category, while the other three aspects, namely observational comparison, social feedback, and physiological state were in the medium category. Based on these results, it is hoped that the level of reading self-perception of English language learners in higher education in this context can be improved, one of which is the presence of pedagogical and psychological support that can give a positive effect on self-efficacy assessments in reading.